MOMENTUM PENATAAN ULANG ORGANISASI PEMERINTAH DAERAH KABUPATEN/ KOTA PADA ERA “NEW NORMAL” - Sulthon Rohmadin, S.STP., M.Si; Sadu Wasistiono (Lembaga Riset dan Pengkajian Strategi Pemerintahan (LRPSP), Institut Pemerintahan Dalam Negeri (IPDN), 2020)
The corona virus pandemic requires all sectors to improve and adjust to new normal conditions, and the local Government organization is no exception. Local Governments should take a number of steps to encourage local government organizations to be more effective and efficient in carrying out their duties and functions. This study aims to provide a new concept in the framework of structuring local government organizations in the